Pengaruh Human Resource Development dan Work Life Balance terhadap Organizational Commitment pada Pekerja Generasi Z di Kota Samarinda (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of Human Resource Development and Work Life Balance on Organizational Commitment among Generation Z employees in Samarinda City. Organizational Commitment refers to the extent to which employees have emotional attachment and loyalty to the organization where they work. The issue of low organizational commitment has become a major concern in human resource management, particularly among younger generations who are known for their dynamic nature and high expectations regarding the work environment. This research highlights how Human Resource Development practices such as training, mentoring, and career development, along with the implementation of Work Life Balance policies, can affect employees’ level of commitment to the organization. The study employed a quantitative approach using a survey method by distributing questionnaires to 111 Generation Z respondents working across various sectors. The collected data were analyzed using multiple linear regression with the help of SPSS version 27. The results show that both Human Resource Development and Work Life Balance have a positive and significant influence on Organizational Commitment, both simultaneously and partially